Upaya Banding Administratif Atas Keputusan Tata Usaha Negara Dalam Perspektif Kepastian Hukum (Studi Undang-Undang Nomor 30 Tahun 2014 Tentang Administrasi Pemerintahan) - M. Naufal; Jamri; Herdiansyah (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2026)
This study aims to analyze the regulation of administrative appeals against State Administrative Decisions under Law Number 30 of 2014 on Government Administration, examine administrative appeals from the perspective of legal certainty, and identify the factors affecting their effectiveness. This research employs a normative legal research method using statutory, conceptual, and case approaches. The findings indicate that Law Number 30 of 2014 provides a legal basis for administrative appeals as a form of legal protection prior to litigation before the State Administrative Court. However, the existing regulation does not comprehensively govern the examination procedures, resulting in potential legal uncertainty. The effectiveness of administrative appeals is influenced by legal substance, institutional structure, legal culture, compliance with the General Principles of Good Governance, and the harmonization of legislation. Therefore, strengthening the regulatory framework and institutional capacity is essential to ensure legal certainty in the settlement of administrative disputes.